The impact of frequency-specific music stimulation on consciousness in patients with disorders of consciousness - Haitao Yang; Wenhao Huang; Wei Wen; Shoufeng Long; Yujie Zhang; Xiangfeng Chi; Daihong Luo (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to evaluate the effects of frequency-specific music stimulation on the awareness and brain connectivity in patients with disorders of consciousness (DOC).MethodsA total of 25 DOC patients were exposed to auditory stimulation through music at varying frequencies (low: <0.5 Hz, middle: 0.5 Hz–3.5 kHz, high: >3.5 kHz). Brain responses were assessed using Functional Near-Infrared Spectroscopy (fNIRS) to monitor objective markers of brain activity. The analysis focused on effective connectivity and coupling strength (CS) values in response to different frequency stimulations, targeting regions such as the motor and somatosensory cortices.ResultsThe mean age of the patients was 49.4 years, with an average coma duration of 1.96 months. While no significant differences were observed in general brain arousal across different frequency stimuli, notable differences in effective connectivity were identified. High-frequency stimulation resulted in significantly higher CS values in the right primary motor cortex (p < 0.05), while middle-frequency stimulation showed significant effects in the right primary somatosensory cortex (p = 0.016).ConclusionThe findings suggest that middle- and high-frequency music stimulation may enhance effective connectivity in specific brain regions, potentially contributing to the rehabilitation of DOC patients. These results indicate that frequency-specific music could stimulate motor networks and areas associated with autobiographical memory, highlighting its therapeutic potential in promoting awareness in this patient population.